2003
DOI: 10.1111/j.1745-7599.2003.tb00331.x
|View full text |Cite
|
Sign up to set email alerts
|

Case Study of Hip Fracture in an Older Person

Abstract: Careful physical and psychosocial assessment is important for determining the presenting problem and comorbid conditions. Priorities for postoperative management of hip fracture and its complications guide the nurse practitioner through the successful return of the patient to the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“… Quantitative Prospective cohort study Public health Inpatient and outpatient Persons affected by a long lie and found alive n = 297 Persons affected by a long lie and found dead n = 90 No definition Häcker & Offterdinger (2019) [ 31 ] GER How is a long lie related to a cardiac arrest? Unclear Case description Emergency medicine Inpatient Person affected by a long lie (5d) n = 1 Persons are unable to move on their own and lie in a helpless position for a longer period Hayes et al (2003) [ 32 ] USA How are older adults treated with a hip fracture? Unclear Case description Rehabilitation Medicine Inpatient Person affected by a long lie (20 h) n = 1 Persons are unable to move on their own and lie on the floor for a longer period Hierholzer et al (2011) [ 33 ] GER What complications can be expected with a long lie?…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… Quantitative Prospective cohort study Public health Inpatient and outpatient Persons affected by a long lie and found alive n = 297 Persons affected by a long lie and found dead n = 90 No definition Häcker & Offterdinger (2019) [ 31 ] GER How is a long lie related to a cardiac arrest? Unclear Case description Emergency medicine Inpatient Person affected by a long lie (5d) n = 1 Persons are unable to move on their own and lie in a helpless position for a longer period Hayes et al (2003) [ 32 ] USA How are older adults treated with a hip fracture? Unclear Case description Rehabilitation Medicine Inpatient Person affected by a long lie (20 h) n = 1 Persons are unable to move on their own and lie on the floor for a longer period Hierholzer et al (2011) [ 33 ] GER What complications can be expected with a long lie?…”
Section: Resultsmentioning
confidence: 99%
“…Older adults suffered falls [ 19 – 21 , 23 28 , 30 , 32 41 ], but it has been the frailty of the individuals that affected their inability to get up after the fall [ 22 28 , 30 , 33 – 36 , 39 ]. Older adults are characterized mainly by balance and mobility problems [ 27 , 28 , 36 , 39 ], they have generally a longer disease duration with poor health [ 27 , 29 ], and are dependent on others for help with activities of daily living [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations